Prinsip Syura Dalam Kepemimpinan Politik Khulafaur Rasyidin Dan Relevansinya Terhadap Politik Islam Kontemporer - Fauziah Amna Sipahutar; Roudhatul Rizka Hasanah; Marzuki (JUSTNESS - Jurnal Hukun Politik dan Agama, 2026)
The relevance of political thought during the Khulafaur Rasyidin era (Abu Bakar ash-Shiddiq, Umar bin Khattab, Utsman bin Affan, and Ali bin Abi Thalib) to contemporary politics. The study shows that the principles of government applied during that era, such as deliberation (shura'), social justice, and accountability of leaders are in line with the values ​​of modern democracy. Through a qualitative approach and historical analysis, this study identifies how the concept of the Medina Charter and the leadership practices of the Khulafaur Rasyidin were able to become models of an egalitarian and participatory political system.The study reveals that despite the distortion of the political system into a dynastic monarchy in the following period, the basic values ​​of the Khulafaur Rasyidin government remain relevant as an inspiration for contemporary Islamic politics. In the modern context, these principles have been adapted by various Muslim movements and thinkers to build a responsive and just system of government. This study concludes that the political thoughts of Khulafaur Rasyidin not only have historical value, but also make significant contributions to the development of a contemporary political system based on Islamic and democratic values. Keywords: Khulafaur Rasyidin, Islamic Politics, Leadership, Justice.